Efficient and Magnetically Recoverable "Click" PEGylated γ‐Fe2O3–Pd Nanoparticle Catalysts for Suzuki–Miyaura, Sonogashira, and Heck Reactions with Positive Dendritic Effects. Issue 4 (26th November 2014) - Wang, Dong; Deraedt, Christophe; Salmon, Lionel; Labrugère, Christine; Etienne, Laetitia; Ruiz, Jaime; Astruc, Didier
Abstract The engineering of novel catalytic nanomaterials that are highly active for crucial carbon–carbon bond formations, easily recoverable many times, and biocompatible is highly desirable in terms of sustainable and green chemistry. To this end, catalysts comprising dendritic "click" ligands that are immobilized on a magnetic nanoparticle (MNP) core, terminated by triethylene glycol (TEG) groups, and incorporate Pd nanoparticles (PdNPs) have been prepared. These nanomaterials are characterized by transmission electron microscopy (TEM), high‐resolution TEM, inductively coupled plasma analysis, Fourier transform infrared spectroscopy, X‐ray photoelectron spectra and energy‐dispersive X‐ray spectroscopy. They are shown to be highly active, dispersible, and magnetically recoverable many times in Suzuki, Sonogashira, and Heck reactions. In addition, a series of pharmacologically relevant or natural products were successfully synthesized using these magnetic PdNPs as catalyst. For comparison, related PdNP catalysts deposited on MNPs bearing linear "click" PEGylated ligands are also prepared. Strong positive dendritic effects concerning ligand loading, catalyst loading, catalytic activity, and recyclability are observed, that is, the dendritic catalysts are much more efficient than non‐dendritic analogues.